The Symbiotic Relationship Between Scientific Quality and Animal Research Ethics. (5th August 2021) - Brill, Samuel A; Guerrero-Martin, Selena M; Metcalf Pate, Kelly A
Abstract: Researchers have worked with animals as models for decades to expand our knowledge of basic biological processes and to systematically study the physiology of disease. In general, the public has an expectation that work with animals has a purpose and will ultimately reap benefits. The likelihood of such an outcome is directly dependent on the quality of the science being conducted with those animals. However, not all frameworks for consideration of the ethics around animal research overtly consider scientific quality. In the following review, we explore the complex relationship between scientific quality and animal research ethics. We advocate for the development of a detailed "Harm-Yield Analysis" for the evaluation of biomedical animal research that emphasizes scientific quality along with societal benefit in the ethical justification of the research. We reflect on the lost opportunity to establish best practices in animal research early in the career of scientists by introducing in the curriculum and encouraging the use of a paradigm of the iterative consideration of the ethics of animal research alongside other aspects of experimental design.